MERESPON TRADISI SESAJEN DALAM PERSPEKTIF HADITS - Ali Mohtarom (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
The practice of offerings is a communit y tradition related to the magical customs or habits of the life of an indigenous population, namely in the form of serving food and other objects that are offered in religious ceremonies or ceremonies carried out symbolically with the aim of communicating with supernatural powers. In responding to tradition and culture, Hadith does not just reshuffle, but responds with three models: Tahmil, Taghyir and Tahrim. If it is in the context of living together, then the context of responding to socio - cultural trad itions and culture, the community must prioritize the love of peace, generosity and high awareness towards anyone in need regardless of their religious background, not cursing the gods (other than Allah) they worship and consider them good. their work.